Understanding the mechanism of anti-carcinogenic effects of Tualang honey (TH) on DMBA (7,12-Dimethylbenz(O)anthracene)- induced breast cancer in rats - Othman, Nor Hayati (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2016)
Introduction: The multifloral Tualang Honey (TH) and the monofloral Manuka Honey (MH) have been reported to have antimicrobial, anti-inflammatory, antioxidant and anticancer effects. Unlike the MH, TH is not extensively studied. Objectives: This study was conducted to evaluate the mechanisms of the preventive and therapeutic effects of Tualang honey (TH), Manuka honey (MH) and honey sugars analogue (HSA) on experimental breast cancer induced rats using carcinogen 1-methyl-1-nitrosourea (MNU). Methodology: A total of 130 female Sprague-Dawley rats were used. Sixty female rats were randomly divided into 6 groups with 10 animals per group in each study. Group '0' (negative control; normal rats); Group 1 (positive control; tumour induction but no treatment). Groups 2, 3 and 4 were fed orally with 0.2, 1.0 and 2.0 g/kg body weight of TH. Group 5 received 1.0 g/kg of MH, and Group 6 received 1.0 g/kg HSA. For the "cancer-preventive" study, honey was given one week prior to MNU-induction and for the "cancer-therapeutic" study; treatment was given after breast cancer development. The treatment continued until the 120th day when the rats were sacrificed for samples collections. Results: Results showed that TH and MH treated rats of "cancer-preventive" groups had a lower tumor incidence, and a longer latency period compared to the non-treated control group. The tumors developed in all treated groups of preventive and therapeutic measures were lesser in number, size and weight compared to the non-treated control. The majority of the tumors in the treated groups were of better grade (grade I and II) compared to the non-treated control group (grade III). The haematological parameters showed that varying strengths of TH, MH and HSA had a potentiating effect on haemoglobin, red blood cells, packed cell volume, mean corpuscular volume, lymphocytes and eosinophils, and a lowering effect on total white blood cells, red cell distribution width , polymorphs, monocytes and platelets compared to the non-treated control. These treatments showed no hyperglycemic effects and no body weight loss. The systemic administration of TH, MH and HSA exerts anti-cancer effects through up-regulation of the expression of pro-apoptotic proteins such as caspase 9, Apfa-1 (apoptotic protease activating factor 1), p53, IFN-y (interferon gamma) and I FNGR 1 (interferon gamma receptor 1), and a concomitant down-regulation of the expression of antiapoptotic proteins such as Bcl-xl (8-celllymphoma-extra large), TNF-a (tumor necrosis factor alpha), COX-2 (cyclooxygenase-2), E2 (estradiol) and ESR1 (estrogen receptor 1) at serological and or breast cancer tissues levels. Discussion: Our study shows that the treatment with TH and MH appears to exert cancer-preventive and or cancer-therapeutic effects, is through the modulation tumour grading, body weight, haematological parameters of immune regulatory response, and modulation of pro and anti-apoptotic proteins of mitochondrial apoptotic pathway at serum and breast cancer tissues level. HSA also acts akin to honey. Conclusion: Tualang honey, Manuka honey and honey sugars analogue can be used as prophylactic cancer and cancer-therapeutic agents. The mechanism is through the modulation of tumour grading, haematological 1 and the modulation of pro and anti-apoptotic proteins at serum and cancer tissues level.